The Influence of Comorbidities on Outcomes of Pulmonary Rehabilitation Programs in Patients with COPD: A Systematic Review. (26th December 2013) - Hornikx, Miek; Van Remoortel, Hans; Demeyer, Heleen; Marcal Camillo, Carlos Augusto; Decramer, Marc; Janssens, Wim; Troosters, Thierry
Abstract : Introduction . Chronic obstructive pulmonary disease (COPD) is associated with comorbidities such as cardiovascular disease, metabolic disease, osteoporosis, and anxiety and/or depression. Although pulmonary rehabilitation programs are proven to be beneficial in patients with COPD, it is unclear whether comorbidities influence pulmonary rehabilitation outcomes. The aim of the present review was to investigate to what extent the presence of comorbidities can affect pulmonary rehabilitation outcomes. Methods . The systematic literature search (Pubmed, EMBASE, and PEDro) resulted in 4 articles meeting the inclusion criteria. The odds ratios (95% confidence intervals) of the logistic regression analyses, with comorbidities as independent variables and pulmonary rehabilitation outcomes (dyspnea, functional exercise capacity, and quality of life) as dependent variables, were used for data extraction. Results . Patients with anxiety and/or depression less likely improve in dyspnea. Osteoporosis is associated with less improvements in functional exercise capacity, while cardiovascular disease does not seem to negatively impact on this outcome. Patients with cardiovascular comorbidity will experience less positive changes in quality of life. Conclusion . Evidence from literature suggests that comorbidities can have a negative influence on pulmonary rehabilitation outcomes. Screening for comorbidities in pulmonary rehabilitation settings seems useful to readdress the right patients for individually tailored pulmonary rehabilitation.